Priority areas for the use of solar water disinfection (SODIS) in Brazil: a spatial approach - Nakada, Liane Yuri Kondo [UNESP]; Urban, Rodrigo Custodio [UNESP] (IWA Publishing, 2024)
This paper presents a methodology for the development of a potential and priority use map for the application of the solar water disinfection (SODIS) method in Brazil. The assessment of solar radiation was conducted, with a particular focus on the annual average global horizontal irradiance (GHI). The water vulnerability index (WVI) and the economic-social-ecosystemic (ESE)-WVI were developed and employed as indicators to define the priority regions for the application of SODIS. The combination of the GHI and WVI maps yielded a SODIS usage potential index (SUPI). The combination of the SUPI map with information pertaining to the human, economic, and ecosystem dimensions of water vulnerability (ESE-WVI) yielded the SODIS usage priority index. The analysis revealed that the country exhibits favorable levels of solar radi-ation, making the implementation of SODIS a viable option, particularly in the Northeast region. Furthermore, the study identified regions with greater water vulnerability, such as the semi-arid region and some parts of the Amazon, as priorities for the application of SODIS. In con-clusion, SODIS represents a viable water treatment technique for various regions in Brazil, particularly those with abundant solar radiation and concerns regarding water security.
Keywords: global horizontal irradiance; solar water disinfection; water quality; water vulnerability